Hepatic Iron Overload following Liver Transplantation from a C282Y/H63D Compound Heterozygous Donor. (31st May 2018) - Veitsman, E.; Pras, E.; Pappo, O.; Arish, A.; Eshkenazi, R.; Feray, C.; Calderaro, J.; Azoulay, D.; Ari, Z. Ben
Abstract : Hereditary hemochromatosis (HH) is a genetic disease associated with progressive iron overload, eventually leading in some cases to damage of parenchymal organs, such as the liver, pancreas, and heart. Although the gene had been identified (HFE), HH pathogenesis remains to be fully elucidated. We report here, for the first time, a case of inadvertent transplantation of a liver from a donor with C282Y/H63D compound heterozygosity into a nonhemochromatotic 19-year-old Caucasian male recipient with primary sclerosing cholangitis. Progressive iron overload occurred over 1.5 years, as observed in liver biopsies and iron studies, after ruling out secondary causes of iron overload. This case strengthens the hypothesis that the liver, rather than the small intestine, plays a primary role in the maintenance of iron homeostasis.